Case Report: Pushing a Stone in the Lower Common Bileduct into the Duodenum - Saeed, Kamal Ahmed (Sulaimani Journal for Pure and Applied Sciences, 2001)
Stone in the common bile duct ( CBD ) may be asymptomatic or the patient prescent with pain , jaundice &fever and rigor .Fever and rigor are due to cholangitis , the jaundice is eilh.er intermittent or persistant .